Violência : agravos à saúde e fatores associados na população urbana de Cáceres - Mato Grosso, Brasil - Silva, Francisca de Assis (2018)
The knowledge about some populations’ health, related to its worsening and gathered factors, is fundamental to program’s planning and actions in the county, specifically when it refers to populations residing in international frontier line area. Aims: This work aims to estimate and analyze the prevalence of violence and related factors in urban population of Cáceres, Mato Grosso’s state. Methodology: It’s about a transversal-cut study, under populational base, 12-65 aged, chosen by systematic groups’ showing. It was raffled 21 census sectors and 30 residences, totalizing 630 subjects responding to the question list. The outcome “violence” was defined as (1) fire or white weapon using and/or (2) counter-self or counter-others aggression and/or (3) suicide attempts. The explaining of variability was socio-demographic-made, even as religious practices, positivity actions to Non- Transmissible Chronical Diseases, alcoholism and Minor Psychiatric Disorder, auto- rating of the interviewee’s health condition, alcohol abuse in the month and physical exercise practices or not. The reliability of the question list was evaluated by Kappa’s Reliability, by data test-retesting, with the interval of seven days between first and second application; the adequation of the instrument was also verified. It was realized bivariate analysis with chi-squared test, connected to Prevalence Rating as associating measure with its Reliability Intervals of 95% (RI 95%). Outcomings: The prevalence of violence was about 13,6% of happening, 6,7% of them occurring with suicidal ideation among those under 18-aged; the Young were easier reached to it (44,7%, PR = 5,13, 95% 2,84-9,28), like ones in non-white ethnicity (15,5%, PR = 1,16, RI 95% 1,07-1,26), physical exercises practitioners (19,4%, PR = 1,52, RI 95 1,24-1,86) and those with health condition unsatisfactoring considered (23,1%, PR = 2,00, RI 95% 1,61-2,49). Conclusion: The prevalence of violence found in the urban population of Cáceres is of concern, specifically due to the high proportion of suicidal ideation among those under 18 years of age. It is hoped by the findings, to contribute to the strengthening of health politics and their intersectoral relations.